PENGARUH TINGKAT LIKUIDITAS, RASIO HUTANG (DER) DAN PENGEMBALIAN ASSET (ROA)TERHADAP RASIO PEMBAYARAN DEVIDEN PADA PT. TELEKOMUNIKASI INDONESIA TBK. (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2017)
ABSTRACTLiquidity, debtratiosandreturns onasset are importantin a company. Liquidity, debt ratio and return on assets can give a company's financial condition. In this study liquidity, debt ratio and return on assets is used to measure the effect on dividend payou tratios.The method used in this research is descriptive and verification using purposive sampling technique. The unit of analysis is PT. Telekomunikasi Indonesia Tbk. Using financial statement data for the past 8 years, from the year 2002-2010.The results and discussion indicate that the correlation between liquidity with Dividend Payout Ratio is high and negative correlation between Debt signifikan. Correlation with Dividend Payout Ratio is high positive and significant. Correlation between Asset Returns with Dividend Payout Ratio weak negative and insignificant.The f-test results on Liquidity, Debt and Returns on Asset no significant effect on Dividend Payout Ratio simultaneously. Thet test Results Liquidity, Debt and Returns on Asset no significant effect on Dividend Payout Ratio.Keywords: Liquidity, Debt Ratio (DER), Return on Asset (ROA) and Dividend Payout Ratio